Skouy chicken: Enhancing livelihoods, preserving tradition - Chi Nguyen; Menghak Phem; Hoang Hoa; Sothyra Tum; Ngoc Dinh (International Livestock Research Institute, 2025)
In Cambodia, the Asian Chicken Genetic Gains (AsCGG, 2021-2025) project is working to strengthen smallholder poultry farming by improving the indigenous Skouy chicken breed. Implemented in Takeo province, the project empowers farmers through training in breeding, biosecurity, and farm management—aiming to boost productivity, food security, and incomes. With the Participatory Indigenous Chicken Breeding Improvement Program (PICBIP), farmers now produce high-quality, dual-purpose chickens, meeting growing market demand while preserving traditional breeds. AsCGG sets a powerful example of sustainable rural development, combining innovation with community resilience.